Strategies to promote the adoption of sustainable drainage by private developers: a case study from Singapore. Issue 1 (2nd January 2021) - Buurman, J. J. G.; Lee, T. K.; Iftekhar, M. S.; Yu, S. M.
ABSTRACT: Different policy mechanisms to encourage private property developers to adopt sustainable drainage features have been tried in many countries with moderate success. Singapore's ABC Waters Programme encourages the adoption of sustainable drainage by private developers through certification amongst others. However, this has not been implemented by all developers uniformly. Therefore, using Singapore as a case study we analyse the key strategies to promote sustainable drainage features. In-depth interviews with twelve prominent property developers were conducted to understand their knowledge, attitude and adoption behaviour. There were no substantial differences in company characteristics between adopters and non-adopters. Five main types of strategies: right timing, industry engagement, public education, financial incentives, and regulations were suggested to increase the adoption of sustainable drainage features in Singapore. These strategies could be suitable for other countries pursuing similar policy goals as well.